Targeting the spectrum of immune checkpoints in prostate cancer. Issue 10 (3rd October 2021) - Sena, Laura A.; Denmeade, Samuel R.; Antonarakis, Emmanuel S.
ABSTRACT: Introduction : The proven efficacy of the cellular vaccine sipuleucel-T in 2010 led to optimism about immunotherapeutic approaches for the treatment of prostate cancer. Some surmised that prostate cancer might be an ideal target for immune-mediated killing given that the prostate is not an essential organ and expresses unique proteins including prostate-specific antigen, prostate-specific membrane antigen, and prostatic acid phosphatase that could be targeted without side effects. Subsequently, antibodies that inhibit the T cell checkpoints PD1 and CTLA4 were shown to stimulate antitumor immune responses, leading to tumor regression in several cancer types. These therapies have since been tested in several studies as treatments for prostate cancer, but appear to have limited efficacy in molecularly unselected patients. Areas covered : In this review, we discuss these studies and evaluate features of prostate cancer and its host environment that may render it generally resistant to CTLA4 and PD1 blockade. We provide an overview of alternate immune checkpoints that may hold greater significance in this disease. Expert opinion : Combination therapies to target multiple layers of alternate immune checkpoints may be required for an effective immune response to prostate cancer. We discuss combination therapies currently being investigated.